The use of medicinal plants in the trans-himalayan arid zone of Mustang district, Nepal - Chaudhary Ram P; Bhattarai Shandesh; Quave Cassandra L; Taylor Robin SL (BMC, 2010)
Abstract Background This study documents the use of medicinal plants from the Mustang district of the north-central part of Nepal. Traditional botanical medicine is the primary mode of healthcare for most of the population of this district and traditional Tibetan doctors (Amchi) serve as the local medical experts. Methods Field research was conducted in 27 communities of the Mustang district in Nepal from 2005-2007. We sampled 202 interviewees, using random and snowball sampling techniques. After obtaining prior informed consent, we collected data through semi-structured interviews and participant-observation techniques. Voucher specimens of all cited botanic species were deposited at TUCH in Nepal. Results We recorded the traditional uses of 121 medicinal plant species, belonging to 49 vascular plant and 2 fungal families encompassing 92 genera. These 121 species are employed to treat a total of 116 ailments. We present data on 58 plant species previously unknown for their medicinal uses in the Mustang district. Of the medicinal plants reported, the most common growth form was herbs (73%) followed by shrubs, trees, and climbers. We document that several parts of individual plant species are used as medicine. Plant parts were generally prepared using hot or cold water as the 'solvent', but occasionally remedies were prepared with milk, honey, jaggery, ghee and oil. Amchis recommended different types of medicine including paste, powder, decoction, tablet, pills, infusion, and others through oral, topical, nasal and others routes of administration. Conclusions The traditional pharmacopoeia of the Mustang district incorporates a myriad of diverse botanical flora. Traditional knowledge of the remedies is passed down through oral traditions and dedicated apprenticeships under the tutelage of senior Amchi. Although medicinal plants still play a pivotal role in the primary healthcare of the local people of Mustang, efforts to ensure the conservation and sustainable use of medicinal species are necessary.